'Primordialism and the 'Pleistocene San' of southern Africa': final reply. (19th July 2016) - Pargeter, Justin; MacKay, Alex; Mitchell, Peter; Shea, John; Stewart, Brian A.
Abstract : We thank our colleagues for their insightful comments. The weight of modern evidence is against the notion that contemporary human cultures can be tracked backwards into the Pleistocene (e.g. Lee & DeVore1976 ; Kuper1988 ; Wilmsen1989 ; Solway & Lee1990 ; MacEachern2000 ). Modern-day hunter-gatherers are not our Stone Age ancestors. Current protestations notwithstanding, the provocative title that d'Errico and colleagues (2012 ) chose for their paper, 'Early evidence of San material culture represented by organic artifacts from Border Cave, South Africa', unambiguously asserts the opposite. Our critique of that paper's content does not question the robusticity of the methods employed at Border Cave (for this, see Evans2012 ). Rather, our comments focus on the theoretically flawed search for a specifically 'San' "cultural adaptation" (d'Errico et al . 2012: 13214) at any Pleistocene archaeological site.